Varanus Species at The Arfak Strict Nature Reserve - FREDDY PATTISELANNO; ENY RAHAYU; JACOBUS WANGGAI (Society for Indonesian Biodiversity, 2007)
The varanid fauna on West Papua particularly have not been well documented, and are poorly known. Survey was conducted in the Arfak Strict Nature Reserve (ASNR) from March to May 2001. During the survey, specimen collected from the field consisted of Varanus indicus (Daudin 1802), Varanus prasinus (Schlegel 1839) and Varanus salvadorii (Peters and Doria 1878). Among three species encountered skin was not utilized, and only Varanus prasinus (Schlegel 1839) meat was not consumed yet.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words:. Varanus, Arfak Strict Nature Reserve